ChemInform Abstract: Facile Synthesis of Ba1‐xKxFe2As2 Superconductors via Hydride Route. Issue 14 (April 2015) - Zaikina, Julia V.; Batuk, Maria; Abakumov, Artem M.; Navrotsky, Alexandra; Kauzlarich, Susan M.
Abstract: Ba1‐x Kx Fe2 As2 (0 ≤ x ≤ 1) superconductors are prepared by high‐energy ball milling of BaH2, KH, and FeAs (containing 6% FeAs2 as impurity) and subsequent annealing (Nb container in evacuated silica tubes, 773—1173 K, 2 d).